2002
DOI: 10.1001/archinte.162.5.582
|View full text |Cite
|
Sign up to set email alerts
|

Systolic vs Diastolic Blood Pressure Control in the Hypertensive Patients of the PAMELA Population

Abstract: In the PAMELA population, SBP control by treatment was much less frequent than DBP control by treatment. This was the case not only for office BP values but also for home and 24-hour BP values, demonstrating that inadequate SBP control is not limited to artificial BP-measuring methods but occurs in daily life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 25 publications
7
43
1
1
Order By: Relevance
“…26 -28 Despite the development of strict treatment guidelines, BP is still inadequately controlled in a large proportion of treated hypertensives. 29,30 The present study confirms a high prevalence of mild hypertension in the elderly and additionally illustrates the risk associated with a moderately elevated BP (mean BP in the sustained hypertensive group, 155/87 mm Hg).…”
Section: Discussionsupporting
confidence: 84%
“…26 -28 Despite the development of strict treatment guidelines, BP is still inadequately controlled in a large proportion of treated hypertensives. 29,30 The present study confirms a high prevalence of mild hypertension in the elderly and additionally illustrates the risk associated with a moderately elevated BP (mean BP in the sustained hypertensive group, 155/87 mm Hg).…”
Section: Discussionsupporting
confidence: 84%
“…Some studies have suggested that discrepancies in cardiovascular risk between males and females may involve genderrelated differences in response to antihypertensive therapy. [18][19][20] For example, a large registry study involving 29 148 essential hypertensive patients receiving antihypertensive treatment found that a greater proportion of women achieved BP control, measured by ambulatory BP monitoring, compared with men. 31 However, a meta-analysis of data from 31 trials involving more than 100 000 male and nearly 90 000 female patients with hypertension found no evidence of a difference in the effects of BP-lowering treatment regimens between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…The study also provides an opportunity to ascertain whether the combination is effective in specific patient groups. For example, certain BP-lowering treatment regimens have been reported to differ between men and women, [18][19][20] whereas others have shown no evidence of a gender difference. 21 Also, BP is known to increase with advancing age and it is important to determine that antihypertensive therapies are effective in older patients.…”
Section: Introductionmentioning
confidence: 99%
“…46 Similarly, PAMELA, a study conducted in Northern Italy, reported a similar poor SBP response rate, with SBP control occurring in 8.9% of treated hypertensives, compared with 15.4% for DBP. 47 Indeed, even in the recently completed ALLHAT study, SBP control occurred in 60% of hypertensive patients vs 90% for DBP control. According to a recent review of 10 antihypertensive drug trials, DBP was invariably below 90 mmHg in most trials, whereas SBP remained above or slightly below 140 mgHg-approximately 90% of patients attained goal DBP values but only 50% attained SBP goal.…”
Section: Overview Of Managing Systolic Hypertensionmentioning
confidence: 99%